1998
DOI: 10.5032/jae.1998.01028
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and Obstacles for Distance Education in Agricultural Education

Abstract: A nationwide study using delphi techniques was conducted to develop consensus andprovide focus and direction for future research activities concerning the adoption of electronic communication, information, and imaging technologies for instructional use in agricultural education settings. A panel of 61 distance education experts were identified The four objectives were to identify the: I)positive effects of electronic technologies designed to facilitate communication, information gathering/retrieval, and imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 7 publications
4
33
1
1
Order By: Relevance
“…In addition, students in North Carolina used the Internet one to 30 minutes daily. These lists closely parallel the list of technologies identified by Murphy and Terry (1998) as showing promise for use in secondary school agricultural education programs. Thompson and Connors (1998);andMiller (1998 &1999) found similar results from secondary agricultural education teachers regarding computer access.…”
Section: Conclusion Implications and Recommendationsmentioning
confidence: 92%
See 2 more Smart Citations
“…In addition, students in North Carolina used the Internet one to 30 minutes daily. These lists closely parallel the list of technologies identified by Murphy and Terry (1998) as showing promise for use in secondary school agricultural education programs. Thompson and Connors (1998);andMiller (1998 &1999) found similar results from secondary agricultural education teachers regarding computer access.…”
Section: Conclusion Implications and Recommendationsmentioning
confidence: 92%
“…Of access locations at school, the library was highest, followed by computer lab, classroom, and office (Thompson & Connors, 1998). Murphy and Terry (1998) identified interactive computer software programs, presentation software, interactive CD-ROM programs, email, computers in the classroom, LDC panels and projectors, CAD programs, video tapes, interactive video, the Internet, and two-way interactive television as instructional technologies that show promise for secondary school agricultural education programs.…”
Section: Instructional Technology Historical Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have studied a sundry of topics related to distance education. Agriculture educators began their approach to understanding online learning by first identifying opportunities and obstacles related to online learning (Miller, 1995;Murphy & Terry, 1998;Murphrey & Dooley, 2000). Similar to other disciplines, agriculture educators also compared on-and off-campus courses (Miller & Shih, 1999;Miller & Pilcher, 2001;Moore & Wilson, 2005) and identified relevant educational technologies that would support online learners (Murphy & Terry, 1998, Murphy, 1999Dooley & Murphy, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…A nationwide study conducted by Murphy and Terry (1998) regarding technology use for instruction concluded that "[e]lectronic communication, information, and imaging technologies [would] improve how we teach in agricultural education settings" (p. 34). While the authors agreed that various technologies would be adopted at different rates, technology was predicted to increase access to information and provide "teaching aids to … meet the needs of the diverse learning styles of students" (p. 31).…”
Section: Findings Historical Backgroundmentioning
confidence: 99%